Vindelevskatten: Et dynastisk offer fra folkevandringstiden - Ravn, Mads; Otte Laursen, Kent (Kuml, 2025)
The Vindelev hoard A dynastic offering from the Migration period The discovery of an amazing gold hoard in Vindelev, a small and to date largely archaeologically unknown village near the later royal seat of Jelling, has shed light on a powerful dynasty in southeastern Jutland, four centuries before the Viking Age and the Jelling Dynasty. The hoard was discovered in 2020 by two amateur archaeologists. It comprises 23 gold objects, including the world’s largest gold bracteate, Roman medallions and other artefacts dating to the Late Roman and Germanic Iron Ages (c. AD 335-550). It has a total weight of 795.6 g. Following the hoard’s discovery, archaeologists from Vejlemuseerne excavated around the deposition site. Although of limited extent, the excavation nonetheless revealed the remains of an apparently typical longhouse within a similarly typical settlement. The Vindelev hoard’s closest parallel is a bracteate hoard from a longhouse in Rugbjerg, West Jutland. The seemingly ordinary character of the house and settlement here contrasts with the extraordinary nature of the hoard. It is the largest known bracteate hoard by weight and contains six out of the 12 largest known bracteates in Scandinavia. Furthermore, it is the first instance of bracteates being found together with Roman gold medallions. These gold medallions are indicative of an extensive European elite network and are associated with two of the largest known gold hoards outside the Roman Empire. We interpret the Vindelev hoard’s internal chronology, spanning two centuries, as evidence that these objects were prestigious heirlooms, exceptional items associated with the upper echelons of society. We perceive the hoard as an indication of the prolonged presence of powerful individuals in Vindelev, possibly in the form of a dynasty. Based on the motifs and stamp identities evident on the bracteates, links to other parts of Denmark become apparent. Similarities with bracteates at elite centres at Odense and Gudme are especially interesting as expressions of contacts between regional elites on Funen and in South Jutland. The distinctive features of the A-bracteates suggest that an early innovation centre for bracteate iconography may have existed in Vindelev or its immediate vicinity, with craftsmen as creative and early in their work as those on Funen. The new variants bearing the twin motif, often highlighted as one of the earliest motifs, could even challenge the idea that this motif originated on Funen. It is, however, doubtful whether a single area where bracteates first emerged could ever be pinpointed. Several objects show signs of ritual destruction: Some are bent, one fragment is twisted into a spiral, and two of the large bracteates have been symmetrically folded along their axes. Most striking of all is the manipulation of the largest known bracteate, X10. Prior to being folded, 1 cm of its entire edge was removed by cutting along a decoration featuring a two-headed snake figure, with the cut passing through the animal’s jaws. We therefore interpret the deposition of the hoard as a sacred act. The date for the deposition, as determined by the typologically latest item, the scabbard mouthpiece, and 14C-dating of the house to the second half of the 6th century, falls within the transitional period between the Early and Late Germanic Iron Age. This was a time marked by natural disasters, epidemics and climate change, and several societal changes took place, such as a reorganisation of settlements around AD 600. We propose that the deposition of the Vindelev hoard was part of a crisis ritual. Its deposition within a house suggests that this ritual was a relatively private undertaking, possibly conducted in connection with the abandonment and reorganisation of the settlement. It likely marked the end of the dynasty that for so long ruled the area around Vindelev. The runes on the bracteates contribute important new information with respect to the meaning of the bracteate motifs. The god Odin is referenced in writing for the first time on X13. The text context, however, refers to another named person, Jagaz, described as “Odin’s man”. If the depicted figure were to be identified with one of the individuals mentioned in the runic text, Jagaz is a likely candidate, being understood as an earthly chieftain or king. The significant aspect from the perspective of religious history, beyond confirming the existence of Odin in the Nordic region already during the Migration period, is its implications for the relationship between Odin and Jagaz, which likely illustrates later known concepts such as elite propaganda about divine ancestry and notions of Valhalla.